Peripheral Vestibular Dysfunction Is a Common Occurrence in Children With Non-syndromic and Syndromic Genetic Hearing Loss - Wang, Alicia; Shearer, A. Eliot; Zhou, Guang Wei; Kenna, Margaret; Poe, Dennis; Licameli, Greg R.; Brodsky, Jacob R. (Frontiers in Neurology, 2021)
Hearing loss (HL) is the most common sensory deficit in humans and is frequently accompanied by peripheral vestibular loss (PVL). While often overlooked, PVL is an important sensory dysfunction that may impair development of motor milestones in children and can have a significant negative impact on quality of life. In addition, many animal and in vitro models of deafness use vestibular hair cells as a proxy to study cochlear hair cells. The extent of vestibular end organ dysfunction associated with genetic pediatric hearing loss is not well understood. We studied children with a known genetic cause of hearing loss who underwent routine preoperative vestibular testing prior to cochlear implantation between June 2014 and July 2020. Vestibular testing included videonystagmography, rotary chair, video head impulse testing, and/or vestibular evoked myogenic potentials. Etiology of HL was determined through history, physical examination, imaging, laboratory testing, and/or genetic testing. Forty-four children (21 female/23 male) met inclusion criteria; 24 had genetic non-syndromic and 20 had genetic syndromic forms of HL. Mean age at the time of testing was 2.8 ± 3.8 years (range 7 months – 17 years). The most common cause of non-syndromic HL was due to mutations in GJB2 (n=13) followed by MYO15A (3), MYO6 (2), POU3F4 (2), TMPRSS3 (1), CDH23 (1), TMC1 (1), and ESRRB (1). The most common forms of syndromic HL were Usher syndrome (4) and Waardenburg (4), followed by SCID/reticular dysgenesis (3), CHARGE (2), CAPOS (1), Coffin-Siris (1), Jervell and Lange-Nielsen (1), Noonan (1), peroxisome biogenesis disorder (1), Perrault (1), and Trisomy 21 (1). Overall, 23 patients (52%) had PVL. A larger proportion of children with syndromic forms of HL had PVL (12/20, 60%) compared with children with genetic non-syndromic HL (11/24, 46%), though without statistical significant (p = 0.3). The occurrence of PVL varied by affected gene. In conclusion, PVL is common in children with syndromic and non-syndromic genetic HL undergoing vestibular evaluation prior to cochlear implantation. Improved understanding of the molecular physiology of vestibular hair cell dysfunction is important for clinical care as well as research involving vestibular hair cells in model organisms and in vitro models.